Substrate Modification in Catheter Treatment of Atrial Fibrillation - Stychynskyi, Oleksandr S.; Topchii, Alina V.; Almiz, Pavlo O. (Ukrainian Journal of Cardiovascular Surgery, 2021)
According to modern concepts, atrial fibrillation (AF) occurs when there are triggers affecting the prepared substrate (atrial myocardium) in the presence of modulating factors that contribute to the occurrence of arrhythmia. Catheter treatment of AF has been most successfully developed in the field of affecting triggers (since late 1990s, the most successful was a technique of isolation of pulmonary veins which are the main source of trigger impulses in AF). Over the past two decades, various techniques have also been proposed for influencing the fibrous substrate. The aim. To analyze the most advanced techniques for influencing the fibrous substrate during catheter treatment of AF. Materials and methods. We analyzed the experience of leading electrophysiological centers in this field. Discussion. Modern studies contain various electrophysiological criteria of fibrous myocardium. However, the signal amplitude less than 0.5 mV is considered borderline between healthy and damaged tissues by most authors. The task of the catheter action on the myocardium is to separate the fibrously altered tissue and intact tissue. This can be achieved by isolating the area of fibrosis or by transforming it into a scar tissue incapable of arrhythmogenesis. It should be noted that both methods are associated with the same frequency of the absence of AF paroxysms, which can be regarded as confirmation of the advisability of influencing the substrate. The most important is that exposure of the substrate can significantly reduce the recurrence rate of AF compared to that when the ablation procedure is limited to isolation of the pulmonary veins. Conclusions. Modern methods of influencing the areas of fibrosis in the atria can significantly improve the results of catheter treatment of AF.